Availability, Utilization, and Health Providers' Attitudes Towards Safe Abortion Services in Public Health Facilities of a District in West Bengal, India - Souvik Pyne; T.K.S. Ravindran (Mary Ann Liebert, 2020)
Background: The provision of safe abortion services upholds the realization of justice in sexual and reproductive health. Many state-level studies in India have identified poor availability of abortion services in the public sector and negative attitudes toward abortion among health providers, as potential barriers to access. Materials and Methods: A cross-sectional study was done to document the availability and utilization of medical termination of pregnancy (MTP or abortion) services and to assess public sector health providers' attitudes towards safe abortion. It was carried out in a representative district of West Bengal, using a facility checklist and a validated attitude scale. Results: Only 11 of 42 public health facilities had both trained doctors and equipment to provide MTP services. Twelve facilities provided MTP services, of which only three urban-based secondary-level facilities provided second trimester MTPs. There were female providers in just 2 of the 12 MTP-providing facilities. Among the 64 health providers interviewed, 40% were trained to provide MTP. According to the attitude scale, 38% had a negative attitude toward the provision of safe abortion services. There was no statistically significant association between attitudes of health providers and provision of MTP. However, there appeared to be a subtle process of gatekeeping in operation, such as making MTP conditional on acceptance of contraception, requiring the husband's consent, and so on. Conclusions: The study shows the poor availability of abortion services in public sector facilities in a district of West Bengal, although all public health facilities from the primary health center level upwards are authorized to provide abortion services.